Financial Integration, Technology Transfer, Labor Productivity Growth and Economic Growth on Pre-and-During COVID-19 Crisis: Evidence from G20 Countries - Luki Okta Fahri; Nur Imamah; Ari Darmawan (Jurnal Keuangan dan Perbankan, 2022)
This study investigates the role of financial integration, technology transfer, and labor productivity growth in economic growth pre-and-during the COVID-19 pandemic crisis. The data collected is panel data from 20 countries of the G20 in the period 2018Q4–2021Q1. By using fixed-effects regression, the results showed that foreign direct investment had a significant effect on economic growth during the COVID-19 crisis, while foreign portfolio investment did not. Furthermore, labor productivity growth has been proven to play a role in moderating foreign portfolio investment, foreign direct investment, and technology transfer in pre-crisis economic growth. However, entering into the COVID-19 crisis stage, labor productivity growth is no longer proven to be moderating, due to a major lockdown policy that led to a decline in labor productivity. This study contributes to helping policymakers with various considerations and sets realistic expectations about the role of financial integration and technology transfer in the recovery of economic growth due to the global crisis.